The All-DQ-Domain EMTP - Gibson H.M. Sianipar (Journal of Engineering and Technological Sciences, 2011)
This paper presents an improvement to dq-domain method of calculating electromagnetic transients. The proposed methodology works on dq-domain model for all components of the power system and during all time iterations.  This is a new direction distinct from the old one where the network is invariably modeled in phase-domain. By modeling the network in dq-domain there is no more problem of interfacing machine to network as usually met in the existing method as machine is modeled invariably in dq-domain. Besides eliminating the time consuming transformation procedure between dq-domain to phase-domain or visa versa the new method is able now to fully exploit the infinite stability region of the trapezoidal rule of integration. The prediction/correction procedure of the conventional dq-domain method, which is notoriously known limiting the stability region, is no longer required. Comparing simulations using the new method and ATP, one of the conventional dq-domain version, show perfect conformity for small time step. For long time step while ATP is failing, the new method still converges accurately up to Nyquist's interval.